Evaluating the Mediating Effect of Employee Training on the Link between Employee Empowerment and Organizational Performance - Al Mansoori , Mohamed Abdulla; Nur Aizat, Ahmad (International Journal of Sustainable Construction Engineering and Technology, 2023)
Assessing employee training as a mediator on the relationship between employees’ empowerment and organizational performance offering insights for effective training interventions to further enhance employee empowerment and overall organizational success. Hence, this paper discusses a study on assessing a mediation effect of employee training which act as mediator to the relationship between the employee empowerment constructs with organisational performance construct. Data used to develop this mediation model was from 115 employees of UAE Federal National Council Organization. The model was developed and assessed in SmartPLS software using the concept of PLS-SEM technique of model development. The model was assessed in three processes which are the PLS Algorithm; Blindfolding and Bootstrapping. The results of mediating modelling assessments found that there is no evidence of mediation effect of Employee Training on the relationships of Meaning and Organization Performance and also, between Competence and Organization Performance. However, there is a partial mediation effect of Employee Training on the relationship between Impact and Organization Performance, indicating that Employee Training partially mediates the relationship between Impact and Organization Performance. Additionally, Employee Training fully mediating the relationship between Self-determination and Organization Performance. The table provides insights into the complex relationships within the model, clarifying the role of mediation in explaining the associations between variables. The findings from this study contributes knowledge on the mediation model of employees’ empowerment on organisational performance.